2012
DOI: 10.1016/j.ymgme.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

CFTR mutation analysis and haplotype associations in CF patients

Abstract: Most newborn screening (NBS) laboratories use second-tier molecular tests for cystic fibrosis (CF) using dried blood spots (DBS). The Centers for Disease Control and Prevention’s NBS Quality Assurance Program offers proficiency testing (PT) in DBS for CF transmembrane conductance regulator (CFTR) gene mutation detection. Extensive molecular characterization on 76 CF patients, family members or screen positive newborns was performed for quality assurance. The coding, regulatory regions and portions of all intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Previously, a recombination event was reported to have occurred within intron 22. 25 However, this recombination event was based on population-level data provided by the HapMap project, which used wild-type CFTR and had significantly reduced marker density compared to this study. 48 Newer HapMap releases suggest two possible primary recombination events in the general population: intron 11 and intron 15-intron 16.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previously, a recombination event was reported to have occurred within intron 22. 25 However, this recombination event was based on population-level data provided by the HapMap project, which used wild-type CFTR and had significantly reduced marker density compared to this study. 48 Newer HapMap releases suggest two possible primary recombination events in the general population: intron 11 and intron 15-intron 16.…”
Section: Discussionmentioning
confidence: 94%
“…The intron 15 recombination event in F508del homozygotes is unique to this population, and is not apparent in HapMap populations (which contain a diversity of CFTR haplotypes only ~5% of which is the F508del ancestral haplotype), where a distinct recombination event within intron 22 is observed. 25 …”
Section: Resultsmentioning
confidence: 99%
“…We observed the OAS2 T/C and C/C genotypes (rs2072137; chr12:113440921) to be associated with “typical” disease progression; however, the T/T genotype presented with higher frequency in the slow progressors. It is well documented that SNPs residing within introns, or those upstream or downstream of genes, also have the capacity to be causal [5154]. In fact, in a recent study, Farh and colleagues utilized a fine-mapping algorithm to analyze GWAS data for 21 autoimmune diseases and reported that approximately 90% of all causal variants map to noncoding regions [55].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, SNPs in the non-coding regions of a gene can manifest a higher risk of cancer (20) and can affect mRNA structure and disease susceptibility (21, 22). In the coding region, SNPs may result in a premature stop codon, a nonsense codon in the transcribed mRNA or in a truncated, incomplete and nonfunctional protein product (21). In recent years, it is found that synonymous SNPs are involved in codon usage preference or mRNA splicing (23-25).…”
Section: Discussionmentioning
confidence: 99%